Genera Diversity and Hard Coral (Scleractinia) Cover in Nipah Bay, Pemenang, North Lombok, Indonesia - Aktia, M. Gilang; Amir, Sadikin; Jefri, Edwin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hard corals (Scleractinia) serve as essential reef constructors and offer habitats for numerus marine species. This study aimed to asses the diversity of hard coral (Scleractinia), genera dan percentage of live coral cover in Nipah Bay as fundamental data for sustainable reef management. The research was conducted in July 2025 at three observation stations with two depth levels (3 and 7 meters). Data collection utilized the Underwater Photo Transect (UPT) method, while coral identification employed Coral Finder 2.0 and CPCe (Coral Point Count with Excel extension) software. Result indicated that live hard coral cover ranged between 10.47 % and 46,73%, which according to the ministry of environment Decree No. 4 2001, falls within the demaged to moderate category. A total of 28 genera and 1,859 hard coral colonies were documented, with Porites, Favites, Montipora, and Pocillopora identified as the dominant genera. The diversity index (H’) ranged form 1.67-2.01, mean 1,86; moderate, the evenness index (E) rangged from 0,60-0,78, mean 0,70; high, and the dominance index (D) ranged from 0,17-0,29, mean 0,22; low. These outcomes suggest that the hard coral community in Nipah Bay remains relatively stale and balanced, though shallow regions exhibit degradations likely due antrophogenic pressures and environmental stress. Sustained monitoring and cominity based conservation are recommended to support coral reef resilience and ecosystem health.